ASYMMETRIC PERIFLEXURAL (UNILATERAL LATEROTHORACIC) EXANTHEM - D. Yu. Ovsyannikov; E. A. Degtyareva (LLC "Diagnostics and Vaccines", 2015)
The article gives data about the epidemiology, possible etiology, clinical presentation and diagnosis of a rare infectious exanthematic disease of unknown etiology - asymmetric periflexural exanthem. Observation of the disease in a child of 22 months was presented. The peculiarity of this clinical observation is the spread the 59 Д. Ю. Овсянников, Е. А. Дегтярева. Асимметричная перифлексуральная (односторонняя латероторакальная) экзантема C M Y K 59 59 59 59 rash to the trunk and the contralateral side, and relapsing course of the disease.